2006
DOI: 10.1177/104063870601800317
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary Osteosarcoma in a Prairie Dog (Cynomys Ludovicianus)

Abstract: Abstract. To date, few tumors have been identified in prairie dogs, with odontoma being the most common. Osteosarcoma has been documented in a wide range of species, including a number of rodents. In this case, a locally invasive maxillary osteosarcoma was diagnosed in a prairie dog. Gross examination revealed a pale, tan, lobulated, sessile maxillary mass extending ventrally into the oral cavity from the hard palate and the gingiva surrounding the upper right cheek teeth. The mass invaded the right nasal cavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
6
1
Order By: Relevance
“…Maxillary osteosarcoma, previously demonstrated by Mouser et al (2006), and epiglottal fibrosarcoma previously demonstrated by Suedmeyer and Pace (1994), were not noted in any prairie dog in this study. In one study a gastric adenocarcinoma with hepatic metastasis, a renal adenocarcinoma and an oral squamous cell carcinoma with renal metastasis were found in three captive male prairie dogs (Grinner, 1983).…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…Maxillary osteosarcoma, previously demonstrated by Mouser et al (2006), and epiglottal fibrosarcoma previously demonstrated by Suedmeyer and Pace (1994), were not noted in any prairie dog in this study. In one study a gastric adenocarcinoma with hepatic metastasis, a renal adenocarcinoma and an oral squamous cell carcinoma with renal metastasis were found in three captive male prairie dogs (Grinner, 1983).…”
Section: Discussioncontrasting
confidence: 70%
“…Garner 1999;Phalen et al, 2000;Wagner and Johnson, 2001;Boy and Steenkamp, 2006). Repeated trauma and fractures to the incisors caused by chewing on cage bars, falling from a height or dental trimming with subsequent trauma of the bone surrounding the incisors, resulting in bony changes that impede the tooth growth, have been proposed as possible causes of elodontomas in prairie dogs (Wagner, 1999;Phalen et al, 2000;Capello, 2002Capello, , 2005Capello, , 2008Boy and Steenkamp, 2006). Another suggested cause is chronic intermittent vitamin A deficiency, which experimentally reproduces apical dysplasia and formation of elodontomas of the upper incisors in rats (McDowell et al, 1987;Crossley, 2004).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…They tend to be highly invasive in mice, leading to infiltration of bone and other structures of the head and should therefore be taken into consideration in the list of differentials. A maxillary osteosarcoma has been reported in a prairie dog 56 and an adenocarcinoma of the buccal salivary gland has been described in a Richardson ground squirrel. 57 Electrical injuries are not uncommonly seen in domestic rodents, as a result of chewing on power cables and subsequent direct body contact with an electrical source.…”
Section: Cheek Teethmentioning
confidence: 99%